Pengaruh Media Pembelajaran Audio Visual Dalam Permainan Bola Voli Terhadap Minat Belajar Siswa - Restu Fauziah Hermawan; Evi Susianti; Ega Trisna Rahayu (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine the effect of audio-visual learning media on student interest in physical education learning volleyball game material. This research was conducted using a quantitative approach with a pre-experimental method with one group pretest-posttest. The population in this study selected 445 from 11 classes. The researcher used cluster random sampling technique. The samples used in this study were 2 classes, Class VII G and VII H which collected 80 students. The instrument used in this study was a questionnaire or questionnaire. processing and analysis of research data using SPSS Software Version 24. There are three stages in this study, namely pretest, treatment, and posttest. The average scores obtained from the pretest and posttest are 142.56 and 150.48, respectively, which means that there is an increase in the average results of the pretest and posttest. The results of this study indicate that there is an effect of audio-visual learning media on student interest, this can be seen from the results of hypothesis testing using paired sample tests that the value of Sig.(2-tailed) <0.05, which is 0.044. So it can be said that there is an influence of audio-visual learning media on student interest in learning physical education volleyball game material